The Effects of Caffeine on Lactation - Ashley Orynich; Linda Bobroff (EDIS, 2012)
“Human milk is the preferred food for infants, with exceptional physiological benefits not only for the baby but for the mother as well. Mothers need to be aware, though, that many substances that they consume are excreted in breast milk and can profoundly affect the composition and adequacy of her breast milk. Even caffeine, which many of us consume on a daily basis in our coffee, tea, cola drinks and chocolate, finds its way into breast milk.” This 2-page Family Album Radio transcript was written by Ashley Orynich and Linda Bobroff, and published by the UF Department of Family, Youth and Community Sciences, August 2012.